EFFECT OF HYDRO-ETHANOL LEAF EXTRACT OF MIRACLE PLANT (Bryophyllum pinnatum) ON THE KIDNEY OF STREPTOZOTOCIN-INDUCED DIABETIC ALBINO RATS - Aluko, Idowu; Bamisaye, Fisayo (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Diabetes is a global health concern with increasing prevalence, often leading to kidney complications. This study evaluates the effects of hydro-ethanol leaf extract of Bryophyllum pinnatum on the kidneys of streptozotocin-induced diabetic albino rats. The extract was analysed for its phytochemical constituents. Twenty-five albino rats were divided into five groups (n=5). Twenty (20) of these rats (groups 2-5) were induced intraperitoneally with a single dose of streptozotocin (35 mg/Kg) to cause diabetes. On the third day, diabetes was confirmed. Groups 1 and 2 (basal control and negative control) received 1 ml of distilled water only. Groups 3 and 4 were treated with 25 and 50 mg/Kg of the extract, respectively. Group 5 received 200 mg/Kg Metformin. Treatments lasted for 14 days, after which the animals were euthanised 24 hours after the last treatment. Kidneys were collected and weighed. Serum was prepared to assess kidney biomarkers. Qualitative phytochemical screening revealed the presence of terpenoids, phenol/phenolic acids, tannins, saponins, glycosides, triterpenes, cardiac glycosides, gums, and mucilage, while steroids, alkaloids, anthraquinones, flavonoids, phlobatannins and fixed and fats were not detected. The extract reduced the renal damage indicated by lowered creatinine, total and direct bilirubin concentrations. Additionally, at 50 mg/Kg, it significantly reduced urea and uric acid levels. However, it was less effective in ameliorating the damage caused by electrolyte imbalance in the kidneys of streptozotocin-induced diabetic albino rats. Overall, this extract demonstrated significant renal protective effects in streptozotocin-induced diabetic albino rats.